(untitled) (Eurasian Research Bulletin, 2023)
In this article, the legislation related to land in the Republic of Uzbekistan, the state policy in the effective use of land, and the role of the prosecutor’s control in this direction are discussed. Also, according to the newly introduced regulation, the changes made to the legislation in the field of land were analyzed.